THE RELATIONSHIP OF THE NURSE'S ROLE AS EDUCATOR WITH THE BEHAVIOR OF THE INTERNAL FAMILY TRANSMISSION PREVENTION Pulmonary Tuberculosis (TB) - Luluk Fauziyah Januarti; tri martian ariesta (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Nurses play an important role in helping the process of preventing TB transmission. One of the roles of professional nurses is as a client educator (educator) whose job is to help clients and increase knowledge about health, symptoms of disease and even the actions given, so that changes in behavior occur from patients and families after the health education is carried out. Based on the results of a preliminary study on 10 families with TB patients, 2 families (20%) with good preventive behavior, 3 families (51%) with sufficient preventive behavior and 5 families (50%) with less preventive behavior. This study aims to analyze the relationship between the role of nurses as educators with family behavior in preventing TB transmission. The research design used analytic with cross sectional approach. Population 58 respondents. the number of samples taken is 51 respondents. The sampling technique used is probability sampling with purposive sampling. The research variables of family behavior in preventing transmission of pulmonary tuberculosis and the role of nurses as educators. The data collection technique used a questionnaire sheet. Statistical test using Spearman Rank test with (a=0.05). This research has been ethically tested by the KEPK STIKes team, Ngudia Husada Madura. NO:1166/KEPK/STIKES-NHM?EC/I/2022. The results showed that the behavior of the family in preventing the transmission of pulmonary tuberculosis was mostly enough at 29 (56.9%) and the role of nurses as educators was mostly enough at 26 (51%). Based on the Spearman Rank statistical test with test results (p = 0.000) < (a = 0.05). So it can be concluded that there is a relationship between the role of nurses as educators with family behavior in preventing pulmonary tuberculosis transmission. It is recommended that research be used as a basis for developing knowledge in adding insight into the role of nurses as educators with family behavior in preventing TB transmission.